2016
DOI: 10.1111/sms.12798
|View full text |Cite
|
Sign up to set email alerts
|

Red cell volume response to exercise training: Association with aging

Abstract: Red blood cell volume (RBCV) is a main determinant of cardiorespiratory fitness in healthy individuals. However, it remains controversial to what extent exercise training (ExT) enhances RBCV. Therefore, we sought to systematically review and determine the effect of ExT on RBCV in healthy individuals across all ages. We conducted a systematic search of MEDLINE, Scopus, and Web of Science, since their inceptions until February 2016 for articles assessing the effect of ExT interventions (not including hypoxic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…The changes in BV reported after 6-8 weeks ET (3-4 sessions week −1 ) typically range from 140 to 550 ml (Bonne et al 2014;Helgerud et al 2007;Montero et al 2017Montero et al , 2015aMontero and Lundby 2017b), whereas a meta-analysis reported a mean increase of 267 ml after ~ 15 weeks of ET (range 1-51 weeks) (Montero and Lundby 2017a). A complex interplay of mechanisms causes the BV expansion in ET that may be affected by the training program, the training status of the subjects and their nutritional status (Montero and Lundby 2018;Sawka et al 2000).…”
Section: The Magnitude Of Haematological Adaptationsmentioning
confidence: 99%
“…The changes in BV reported after 6-8 weeks ET (3-4 sessions week −1 ) typically range from 140 to 550 ml (Bonne et al 2014;Helgerud et al 2007;Montero et al 2017Montero et al , 2015aMontero and Lundby 2017b), whereas a meta-analysis reported a mean increase of 267 ml after ~ 15 weeks of ET (range 1-51 weeks) (Montero and Lundby 2017a). A complex interplay of mechanisms causes the BV expansion in ET that may be affected by the training program, the training status of the subjects and their nutritional status (Montero and Lundby 2018;Sawka et al 2000).…”
Section: The Magnitude Of Haematological Adaptationsmentioning
confidence: 99%
“…A fundamental principle of cardiovascular physiology refers to the strict dependence of cardiac reserve upon blood volume (BV), which facilitates venous return, ventricular filling, and stroke volume via the Frank–Starling mechanism (Guyton and Hall ; Bonne et al ; Montero et al ). Indeed, BV is a tightly regulated fluid varying as little as 4% over several months in healthy individuals, plausibly owing to its central role in maintaining whole body homeostasis (Montero and Flammer ; Montero and Lundby ). In the presence of a failing heart, acute fluid retention leading to BV expansion is considered a disproportionate compensatory response in the attempt to retrieve cardiac reserve, eventually resulting in clinical congestion (Guyton and Hall ).…”
Section: Introductionmentioning
confidence: 99%
“…EICR has been thoroughly characterized among elite athletes (2,11,18,19,21,33) and has recently been documented among recreational exercisers who typically perform comparatively lower volumes and intensities of exercise training (1,8,13,28,35). Similarly, the hematologic response to endurance exercise training has been described in novice exercisers where a rapid increase in plasma volume (PV) precedes a slow increase in red blood cell volume (16). A recent meta-analysis concluded that increases in red blood cell volume of 4% can be expected over 15 wk of endurance training in young and middle-aged exercisers (16).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the hematologic response to endurance exercise training has been described in novice exercisers where a rapid increase in plasma volume (PV) precedes a slow increase in red blood cell volume (16). A recent meta-analysis concluded that increases in red blood cell volume of 4% can be expected over 15 wk of endurance training in young and middle-aged exercisers (16).…”
Section: Introductionmentioning
confidence: 99%